ANALISIS PENGGUNAAN MEDIA MINI BOOK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA DAN MENULIS PESERTA DIDIK DI SEKOLAH DASAR - Wahyuni, Holy Ichda; Pentianasari , Sherli (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2024)
This research aims to look at the use of mini book media to improve the reading and writing skills of students at the elementary school Muhammadiyah 2 Surabaya. This research uses a qualitative approach, where data is collected using structured interview techniques and documentation. The informant in this research was a class IV teacher. Data were analyzed using the Miles and Huberman data triangulation model. The results of the research show that mini book media is the media used by fourth grade teachers at SD Muhammadiyah 2 Surabaya in the teaching and learning process in class. This is due to the flexibility of the media in each lesson, as well as the ease of creating and using it in learning and being liked by students.